Development of Tourism Communication Model Based on Local Wisdom in Padangsidimpuan - Tanjung, Irwan Syari; Tanjung, Hasrudy; Wibowo, Yogi Sumarsono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Tourism based on local wisdom can realize community creativity in introducing regional potential, especially culture, as a unique attraction and can support the development of a creative economy for local communities. For this reason, collaboration is needed among stakeholders, local governments (in this case, the Padangsidimpuan City Culture and Tourism office), tourism managers, the community to work together to build tourism based on local wisdom based on available social capital such as networks, culture, and social trust to support coordination and to the common interest. This study uses an experimental method with a qualitative approach. The research subjects are informants, namely the Padangsidimpuan city culture and tourism department employees, local wisdom-based tourism managers in Padangsidimpuan, Padangsidimpuan city communities, and tourists. Research subjects or informants were 11 people. The data collection techniques used are interviews, observations, documentaries, and online data searches. The technique data analysis used is descriptive qualitative and triangulation data analysis techniques as a validity test. This study concludes that it is necessary to develop a tourism communication model that is formed in Padangsidimpuan. There is involvement between the relevant public in the effort to develop tourism based on local wisdom. Statement of attitudes and commitments from all related elements in the tourism sector to maintain socio-cultural values and preserve the environment as the foundation of tourist destinations. Local wisdom managed by managers, audiences, cultural and tourism offices, and other related agencies to become a Padangsidimpuan tourist destination, namely Salak.